Algunos Mitos, Estereotipos, Realidades y Retos de Latinoamérica - Vargas, José (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
Most Latin American scholars treat Latin American nations as a simple study object with similar characteristics. The purpose of this essay is to analyze some myths, stereotypes, realities, and challenges given to one of the most important regions of the world, knowing as Latin America. Latin America has been conceptualize as a homogeneous entity, meaning only the current nations which have received the Spanish heritage as a result of being conquered and colonized by Spain and Portugal. Most part of Latin American studies dismissed to recognize the influence of other cultures of Northern Europe and undervalued the strong heritage received by indigenous cultures or amerindias and the African descendents. Nevertheless, I argue the term Latin America can only be applied weakly and cautiously to the region, being conscious of its geographical diversity, physical environment and its historical, economical, social, cultural, and religious formations. I show how inappropriate is to label to all people and nations in Central America, South America, and the Caribbean as "Latinos" and so I reject the assumption that Latin America represents a uniform culture with the same antecedents, racial similar categories and similar racial, religious, economical, social, and political characteristics.